Exploring Decarbonization Strategies and Sustainable Alternatives for Cement - Ritika Priyadarshani (International Journal of Manufacturing and Production Engineering, 2024)
As one of the most evolving economic sectors, building construction creates wealth and income while making a significant contribution to global development. Almost 40% of all carbon emissions, both direct and indirect, come from this industry. It is crucial to lower emissions from the manufacture of cement to mitigate climate change. The cement industry must be made less carbon-based. The need to address the environmental effects of traditional cement production, which is a significant contributor to global carbon emissions, is what drives this research. The search for sustainable alternatives, such as substitute materials and cutting-edge technologies, is motivated by the urgency of addressing climate change and aligning with Sustainable Development Goals. The principal objective of this research is to support global initiatives that promote creativity, environmental sustainability, and a robust future for the cement sector.
Keywords: Alternative materials; Decarbonization; Sustainable manufacturing: Carbon capture and storage; cement